B‐type olivine fabric and mantle wedge serpentinization beneath the Ryukyu arc. Issue 9 (9th May 2013) - McCormack, Kimberly; Wirth, Erin A.; Long, Maureen D.
<x xml:space="preserve">Abstract</x> [1] Subduction is a fundamental Earth process, yet many aspects of subduction systems remain to be fully understood. Here we present anisotropic receiver function (RF) analysis to characterize the structure of the mantle wedge beneath the Ryukyu subduction zone. Radial and transverse P‐to‐S RFs computed for eight broadband stations yield evidence for coherent P‐to‐SV conversions originating at the top of the subducting slab. We also observe conversions on the transverse component RFs that are consistent with the presence of multiple anisotropic layers, with structure varying significantly along strike. Forward modeling of observations at station ZMM in the center of the Ryukyu arc yields evidence for a 6 km thick layer of strongly anisotropic material, most likely serpentinite, directly above the subducting slab and likely B‐type olivine fabric in the shallow mantle wedge.